1999
DOI: 10.1074/jbc.274.42.29889
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Recognition of Phosphorylated High Mannose Oligosaccharides by the Cation-dependent Mannose 6-Phosphate Receptor

Abstract: Mannose 6-phosphate receptors (MPRs) play an important role in the targeting of newly synthesized soluble acid hydrolases to the lysosome in higher eukaryotic cells. These acid hydrolases carry mannose 6-phosphate recognition markers on their N-linked oligosaccharides that are recognized by two distinct MPRs: the cation-dependent mannose 6-phosphate receptor and the insulinlike growth factor II/cation-independent mannose 6-phosphate receptor. Although much has been learned about the MPRs, it is unclear how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
77
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 41 publications
2
77
0
Order By: Relevance
“…Our recent crystal structure of Asn-81/STOP 155 bound to pentamannosyl phosphate reveals that Tyr-45 interacts with the 1-hydroxyl of Man-6-P, which is involved in an O-glycosidic linkage, and the 4-hydroxyl of the penultimate mannose residue (21). Replacement of Tyr-45 with Phe decreases receptor binding to pentamannosyl phosphate columns by ϳ30% ( Table I), indicating that Tyr-45 is not critical for ligand recognition.…”
Section: Fig 2 Cd-mpr Bound To Man-6-pmentioning
confidence: 99%
“…Our recent crystal structure of Asn-81/STOP 155 bound to pentamannosyl phosphate reveals that Tyr-45 interacts with the 1-hydroxyl of Man-6-P, which is involved in an O-glycosidic linkage, and the 4-hydroxyl of the penultimate mannose residue (21). Replacement of Tyr-45 with Phe decreases receptor binding to pentamannosyl phosphate columns by ϳ30% ( Table I), indicating that Tyr-45 is not critical for ligand recognition.…”
Section: Fig 2 Cd-mpr Bound To Man-6-pmentioning
confidence: 99%
“…domains 3 and 9) of all CI-MPRs sequenced to date, and substitution of Gln-66, Arg-111, Glu-133, or Tyr-143 of the CD-MPR (31) or their corresponding residues in domains 3 and 9 of the CI-MPR (21) results in a decrease in the affinity of the receptor for a lysosomal enzyme by Ͼ1000-fold. The crystal structures of the CD-MPR (13,27) and domains 1-3 of the CI-MPR (28,29) confirm the importance of these residues by demonstrating that their location is within hydrogen bonding distance of the hydroxyl groups of the mannose ring. To evaluate whether equivalent Gln, Arg, Glu, and Tyr are present in other regions of the CI-MPR, we performed a structure-based sequence align- FIG.…”
Section: Discussionmentioning
confidence: 62%
“…Interestingly, this study also revealed that domain 5 exhibits a comparable level of sequence identity to the CD-MPR as observed for domains 3 and 9. Our crystal structures of the CD-MPR (13,27) and domains 1-3 of the CI-MPR (28,29) plus mutagenesis studies (21,30,31) have identified conserved residues that are essential for Man-6-P binding. To evaluate the possibility that domain 5 binds carbohydrate, we performed a structure-based sequence alignment to compare domain 5 with the CD-MPR and domains 3 and 9 of the CI-MPR (see Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, group II carbohydrate-binding proteins, which include lectins, typically bind their ligands in shallow clefts on the protein surface (4). Our recent crystallographic studies of the CD-MPR in complex with ligands containing phosphomannosyl residues reveal that this P-type lectin is unusual with respect to the architecture of its carbohydrate-binding pocket when compared with the majority of animal and plant lectins; the CD-MPR has a relatively deep binding pocket, which essentially buries the terminal sugar ring and phosphate group (5,6). Thus, the CD-MPR displays similarities with the group I, but not the group II, carbohydrate-binding proteins.…”
mentioning
confidence: 99%